The Influence of Green Banking and Corporate Social Responsibility on Firm Value in the Banking Sector Listed on the Indonesia Stock Exchange (2018–2023) - Sari, Olivia; Muslimin, Muslimin (BISMA : Business and Management Journal, 2025)
This research examines the effect of Green Banking and Corporate Social Responsibility (CSR) on the firm value of banking institutions listed on the Indonesia Stock Exchange (IDX) over the period 2018 to 2023. Utilizing a quantitative methodology with purposive sampling, the study selected nine banks that consistently disclosed sustainability reports throughout the study period. The variables Green Banking and CSR were operationalized through their respective disclosure indices, while firm value was measured by the Price to Book Value (PBV) ratio. Data analysis was conducted using panel data regression employing the Random Effects Model. The empirical findings reveal that both Green Banking and CSR exert a statistically significant and positive influence on firm value. Specifically, a 1% increase in Green Banking and CSR disclosure corresponds to an approximate increase of 1.17% and 1.08% in PBV, respectively. These results highlight the critical role of environmental and social governance factors in shaping investor perceptions and enhancing firm valuation. It is recommended that banks enhance transparency and disclosure practices related to Green Banking and CSR to bolster market valuation and promote sustainable corporate growth. This study contributes to the expanding body of literature on sustainable finance and its impact on firm performance within emerging market contexts.